G20 Note On Environmentally Sustainable Investment For The Recovery. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2021)
This Note prepared for the G20 Infrastructure Working Group summarizes the main finding of the IMF flagships regarding the role of environmentally sustainable investment for the recovery. It emphasizes that environmentally sustainable investment is an important enabler for a resilient greener, and inclusive recovery-it creates jobs, spurs economic growth, addresses climate change, and improves the quality of life. It can also stimulate much needed private sector greener and resilient investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Climate Change and Environmentally Sustainable Investment; IMF Flagship; Monetary Policy; Political Economy; Public Investment Management and Green Infrastructure; Transparency Policy